Assessment of hostile and benign intent attributions in early childhood: Can we elicit meaningful information?. Issue 2 (21st November 2017) - Schultz, David; Groth, Elisabeth; Vanderwalde, Holly; Shannon, Katherine; Shuttlesworth, Mary; Shanty, Lisa
Abstract: Throughout middle childhood and adolescence, hostile intent attributions fairly consistently predict levels of aggression. Across 28 published studies in early childhood, however, researchers have found less consistent relationships. We believe this may be due to a majority of these studies using an inappropriate methodological approach for early childhood, forced‐choice questioning. We tested the use of open‐ended vs. forced‐choice questions about intent in 118 Head Start preschool children. In response to a forced choice question, only about 30% of children attributed intent correctly to a video depicting clearly purposeful behavior. And across 18 video vignettes depicting ambiguous provocation, children's intent attribution scores based on a forced‐choice approach demonstrated neither reliability nor validity. Conversely, children's intent attribution scores in response to open‐ended questions demonstrated reliability, correspondence with other aspects of social information processing, and predictive validity in the form of relations to teacher reports of social competence and aggression. Researchers should refrain from utilizing forced‐choice approaches to intent attributions in early childhood unless also conducting intent understanding checks.